The Roots of Young Generation Radicalism: A Study of Citizenship Sociology - Sri Wahyuni Tanshzil; Karim Suryadi; Kokom Komalasari; Leni Anggraeni (Jurnal Civicus, 2022)
The emergence of radicalism in Indonesia is based on two factors, namely the macro level and the micro level. At the macro level, radicalism occurs due to the presence of injustice, and socio-economic inequality, which ends in the perception of the failure of the state in guaranteeing the rights of its citizens to welfare. At the micro level, radicalism arises from within a particular individual or group. This paper aims to examine the roots of youth radicalism and examine it from the perspective of the sociology of citizenship. The type of research used is descriptive qualitative with a systematic review method, namely a research method that summarizes the main research results to be analysed and presented in order to provide accurate, comprehensive, and balanced information. The results of the study show 1) Radicalism is an understanding that wants change and renewal to its roots in social and political ways in an extreme way. 2) The roots of radicalism in the younger generation are indicated by 4 main things, namely mental health, economic inequality, socio-political conditions, and religious commitment, 3) in the perspective of the sociology of citizenship, radicalism is a picture of the failure of a country to prosper its citizens.